PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN FLASH CARD BHINNEKA TERHADAP MINAT BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Shova Anggriani; Yulina Ismiyanti (Universitas Negeri Medan, 2026)
This research is focused on examining the extent to which the application of the Teams Games Tournament (TGT) learning model assisted by Bhinneka Flash Card media influences the interest in learning science in grade IV elementary school students. This study employed a quantitative pre-experimental One Group Pretest Posttest method. The population consisted of 28 students, with a saturated sampling technique, using the entire population as the sample. Data collection included a learning interest questionnaire. Based on the pretest and posttest normality tests the average student interest in learning (pretest) was 47.86, and after treatment, the average posttest score was 60.18. the results showed a paired sample t-test with a Sig. (2-tailed) of 0.000 <0.005. This indicates that H0 is rejected and H1 is accepted. It can be concluded that the implementation of the TGT model, using Bhinneka Flash Cards, can influence the interest in learning science in fourth-grade elementary school students.